(untitled) (The Pakistan Development Review, 2007)
The last few decades have witnessed a significant shift in the concept of development. Research focusing on development has shifted its focus from macroeconomic to more microeconomic development. More recently, poverty has become an important interest area for researchers, governments, United Nations agencies, NGOs and some specialised international development agencies. The United Nations has designated the period 1997-2006 as the decade for poverty eradication [World Summit for Social Development (1995)]. The millennium meeting at the United Nations headquarters and its follow-up meeting at Brussels set up on ambitious target for reducing poverty by half by the year 2015. [Altaf (2004)]. Since the overall objective is “human development,” people are presumed to play a major role in assuming the initiative, management of, and control over resources, as well as the setting of priorities for poverty reduction. The translation of this idea into reality necessitates the investigation of people’s understanding and experiences of poverty and adjustment to, or coping with, chaotic socio-economic situations and catastrophes (both human and natural), be they food insecurity, hunger, famine outbreaks, or poverty. Some of these crises, in many cases, are not occasional occurrences; rather they are the consequences of long term processes, especially poverty, which is caused by a combination of interacting factors related to social, economic, political, and natural dimensions [Abdel (1996)].